1966
DOI: 10.3758/bf03342338
|View full text |Cite
|
Sign up to set email alerts
|

Anagram solution as a function of pronounceability and difficulty

Abstract: The present study investigates the effect of pronounceability (P), as rated by Ss, on anagram solution probability under two levels of difficulty (D) Mayzner & Tresselt (1965) presented evidence that there is no difference in solution times of word and non-word anagrams. This discrepancy of results suggests that perhaps an alternate approach is needed to elucidate the problem of word vs. non-word anagrams.It is reasonable to consider words more pronounceable than non-words. It is equally reasonable to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Replicating earlier research (Dominowski, 1969;Hebert & Rogers, 1966), there was a reliable effect of pronounceability, as participants spent more time on easier to pronounce anagrams (Ms of 17.05 s and 15.40 s, respectively; SDs of 5.32 and 4.76). As predicted, however, this effect was much larger for poor solvers.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Replicating earlier research (Dominowski, 1969;Hebert & Rogers, 1966), there was a reliable effect of pronounceability, as participants spent more time on easier to pronounce anagrams (Ms of 17.05 s and 15.40 s, respectively; SDs of 5.32 and 4.76). As predicted, however, this effect was much larger for poor solvers.…”
Section: Resultssupporting
confidence: 71%
“…The degree to which an anagram letter string is pronounceable is not predictive of the solution because, for example, (a) many pronounceable letter combinations are not words (e.g., zelba, eckho), and (b) a contiguous subset of letters that is pronounceable in an anagram (e.g., aft in aftes) may not make up part of the solution in combination with the remaining letters (the solution is feast). Previous research indicates that anagrams that are easier to pronounce (e.g., aftin as opposed to infta) are harder to solve (the solution is faint; see Dominowski, 1969, andHebert &Rogers, 1966). These studies used unselected college students, who our earlier research suggests are typically poor to fair at solving anagrams (see the Experiment 1 Participants section).…”
Section: Pronounceabilitymentioning
confidence: 99%
“…If it could be shown that mere presentation or spelling practice produces minimal changes in pronunciation speed, a comparison of these types of training with pronunciation practice would be informative. FinaHy, as Hebert & Rogers (1966) suggested,. a consideration of pronounceability.effects provides a·plausible explanation for the finding that word anagrams are more difficult than nonsense anagrams(e.g., Ekstrand & Dorninowski,1%8).…”
mentioning
confidence: 99%
“…With stimuli having weaker populars, however, the idiosyncratic responders tended not to repeat their responses, producing a low degree ofTRR. Hebert & Rogers (1966) reported that anagrams which are easy to pronounce (EP) are more difficult to solve than anagrams that are hard to pronounce (HP). However, the design of their study did not permit an unambiguous conclusion concerning the effect of anagram pronounceability since EP and HP anagrams had different solution words.…”
mentioning
confidence: 99%
“…Novick and Sherman (2008) describe it as "superficial" and something which is more likely to affect poor solvers. Yet the detrimental effect of pronounceability on anagram solution has been demonstrated on many occasions (Herbert & Rogers, 1966;Dominowski, 1966;Gilhooly & Johnson, 1978). It clearly suggests that Anagrams and Syllables phonemic encoding of anagrams takes place and is involved in some way in their solution, just as phonemic encoding plays a part in visual search, word recognition and reading processes (Conrad, 1964).…”
Section: Discussionmentioning
confidence: 99%